Schema Therapy – a powerful tool in management of Borderline Personality Disorder - Kłak, Igor; Szerocki, Jan; Winkowska, Alicja; Grudina, Alina; Bartnik, Katarzyna; Chwaleba, Katarzyna; Milewska-Plis, Katarzyna; Mazur, Ksenia; Herian, Mariola; Karalus, Monika (Quality in Sport, 2025)
Borderline Personality Disorder (BPD) is a clinically significant psychiatric condition characterized by fear of abandonment, emotional and interpersonal instability, identity disturbance, impulsivity, and self-harming or suicidal behaviors. Its etiology involves a complex interplay between genetic predispositions and early developmental trauma, particularly attachment disruptions. BPD is associated with a high risk of suicide and self-injurious behavior. Currently, there is no pharmacological treatment that directly targets the core pathology of BPD; medications are used symptomatically. The gold standard in management is long-term psychotherapy. Schema Therapy (ST) and Dialectical Behavior Therapy (DBT) have demonstrated superior efficacy compared to treatment-as-usual, with ST showing the highest effectiveness in reducing suicidal behaviors. ST is an integrative therapeutic approach that focuses on unmet emotional needs underlying the formation of Early Maladaptive Schemas (EMSs). These schemas elicit maladaptive coping styles, which in turn give rise to transient schema modes. From the ST perspective, BPD emerges from the interaction between innate vulnerability and early, often traumatic, familial experiences. A central feature is the Abandonment/Instability schema. Rapid shifts between coping styles and schema modes are characteristic of BPD, frequently involving activation of the Abandoned Child, Punitive Parent, and Detached Protector modes. Treatment within ST emphasizes limited reparenting, emotion-focused techniques, and mode modification, with the primary goal of fostering the Healthy Adult mode. Schema Therapy is increasingly recognized as one of the most effective psychotherapeutic approaches for treating BPD.